Road to Avonlea. The complete seventh season [videorecording (DVD)]. - Burroughs, Jackie; Ruffman, Mag; Montgomery, L. M. (Lucy Maud), 1874-1942; Bennett, Zachary; Smith, Cedric (Sullivan Entertainment, 2012)
In this dramatic season, the King family copes with difficult personal and community changes that threaten to change their lives forever. Road to Avonlea's final season is the dramatic culmination of over seven years of excellence in dramatic programming.